2015
DOI: 10.1039/c4ra10241j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of precursor on the formation of different phases of iron oxide nanoparticles

Abstract: Trioctylamine is known to act simultaneously as a reducing as well as a hydrolyzing agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
4
13
0
Order By: Relevance
“…In 3 and 4, the peaks at ca. 1400 cm −1 can be associated to iron oxyhydroxide [17], while the bands at 1229, 1140, 998, and 626 cm −1 are related to the S=O group [18,19]. These results relate well with the data obtained by thermogravimetric analysis ( Figure S4), where elimination of the coordinated water and hydroxy groups can be observed at 100-300 • C while the S=O group decomposition occurs at 500-700 • C.…”
Section: Characterization Of the Dispersed Materialssupporting
confidence: 86%
See 1 more Smart Citation
“…In 3 and 4, the peaks at ca. 1400 cm −1 can be associated to iron oxyhydroxide [17], while the bands at 1229, 1140, 998, and 626 cm −1 are related to the S=O group [18,19]. These results relate well with the data obtained by thermogravimetric analysis ( Figure S4), where elimination of the coordinated water and hydroxy groups can be observed at 100-300 • C while the S=O group decomposition occurs at 500-700 • C.…”
Section: Characterization Of the Dispersed Materialssupporting
confidence: 86%
“…The catalytic system 3 appears to be the one that preferably responds to ultrasound activation (Table 4, entries [11][12][13][14][15]. Finally, the catalyst 4 responds equally to all three types of activating inputs (Table 4, entries [16][17][18][19][20]. For comparative purpose, oxidation of 1-phenylethanol to acetophenone was also performed by mechanochemical treatment (500 rpm, 10 spheres of 10 mm diameter, with rotational inversions every 5 min) in the presence of 1-4, at room temperature (Table 4, entries 5, 10, 15, and 20).…”
Section: Effect Of the Energy Inputmentioning
confidence: 99%
“…Kumar et al also elucidated the effects of precursors in the formation of different forms of iron oxide and oxyhydroxide by using trioctylamine as the reducing agent in a coprecipitation process. [71] Their results showed that the constitution, shape, size, and properties of phases significantly changed by changing the cations. Topel el al.…”
Section: Coprecipitationmentioning
confidence: 99%
“…Different procedures have been developed for the preparation of IONPs, either by physical, chemical, or biological pathways, each with their advantages and disadvantages [57]. Physical procedures consist of gas phase deposition, electron-beam lithography, pulse laser ablation, laser-induced pyrolysis, powder ball milling, and aerosol [58,59].…”
Section: Synthetic Pathways To Ionpsmentioning
confidence: 99%
“…For IONPs, specific bacteria-magnetotactic bacteria and iron reducing bacteria-are used [3]. The main chemical methods are coprecipitation, solvothermal, hydrothermal, microwave irradiation, thermal decomposition, sonochemical, inverse microemulsion, sol-gel synthesis, flow injection, and electrospray synthesis [57,[59][60][61]. One of the most common methods to prepare IONPs is the coprecipitation of Fe +2 and Fe 3+ precursors in strong alkaline medium.…”
Section: Synthetic Pathways To Ionpsmentioning
confidence: 99%